The Impact of Inflow Angle on Aneurysm Hemodynamics: A Simulation Study Based on Patient-Specific Intracranial Aneurysm Models - Mo, Xiao; Meng, Qianqian; Yang, Xinjian; Li, Haiyun (Frontiers in Neurology, 2020)
The inflow angle of intracranial aneurysms (IAs) can impact the hemodynamics of IAs, hence is likely to contribute to IAs clinical rupture risk stratification. This study aimed to assess the effect of inflow angle on the hemodynamics of IAs, as well as its potential ability to predict IA rupture risk. A novel algorithm was developed to build a series of inflow angle models on patient-specific IA models, which were reconstructed from IA 3DRA image data of eleven clinical patients. Fully coupled fluid-structure interaction (FSI) simulations were performed to quantify hemodynamic characteristics of the established IA models with varied inflow angles. Hemodynamic parameters including wall shear stress (WSS), flow velocity, flow pattern, inflow zone, impingement region, pressure, and Energy loss (EL)), were calculated and analyzed. It was demonstrated from the analysis that a rise in the IAs inflow angle can lead to the follow hemodynamic changes: more direct blood flowed into the aneurysm sac, higher velocity at the upside of the aneurysm, up-regulated flow velocity and WSS in the aneurysm, more complicated flow patterns, extended inflow zone, the impingement region moving upward from the neck to the apex of the aneurysm, and higher WSS and larger flow velocity at the inflow zone of the IAs. Therefore, the proposed method is helpful in exploring the hemodynamics variations of IAs with the inflow angle. The findings could be conducive to hemodynamics studies on the association between IA inflow angle and its rupture risk.